That's not what you expect to do as a doctor, you know, you don't expect your patients to die." Death as a learning experience for undergraduate medical students. Issue 1 (December 2016) - Smith-Han, Kelby; Martyn, Helen; Barrett, Anthony; Nicholson, Helen
Abstract Background Experiencing the death of a patient can be one of the most challenging aspects of clinical medicine for medical students. Exploring what students' learn from this difficult experience may contribute to our understanding of how medical students become doctors, and provide insights into the role a medical school may play in this development. This research examined medical students' responses of being involved personally in the death of a patient. Method Ten undergraduate medical students were followed through their three years of clinical medical education. A total of 53 individual semi-structured interviews were conducted. Grounded theory analysis was used to analyze the data. Results Students illustrated a variety of experiences from the death of a patient. Three main themes from the analysis were derived: (i) Students' reactions to death and their means of coping. Experiencing the death of a patient led to students feeling emotionally diminished, a decrease in empathy to cope with the emotional pain and seeking encouragement through the comfort of colleagues; (ii) Changing perceptions about the role of the doctor, the practice of medicine, and personal identity. This involved a change in students' perceptions from an heroic curing view of the doctor's role to a role of caring, shaped their view of death as a part of life rather than something traumatic, and resulted in them perceiving a change in identity including dampening their emotions; (iii) Professional environment, roles and responsibilities. Students began to experience the professional environment of the hospital by witnessing the ordinariness of death, understanding their role in formalizing the death of a patient, and beginning to feel responsible for patients. Conclusions Along with an integrative approach to facilitate students learning about death, we propose staff development targeting a working knowledge of the hidden curriculum. Knowledge of the hidden curriculum, along with the role staff play in exercising this influence, is vital in order to facilitate translating the distressing experiences students face into worthwhile learning experiences. Finally, we argue that student learning about death needs to include learning about the social organization and working life of clinical settings, an area currently omitted from many medical education curricula.